The Ideal Model For Countermeasures Of Sexual Violence In The Universities Environment - Surya Nagara, Airlangga; Adi, Elisabeth Ayu Puspita (UI Scholars Hub, 2024)
This Cases of sexual violence are rife, including in universities. Data compiled by Komnas Perempuan shows that during 2015-2021, out of 67 reported cases of sexual violence against women, 35 cases occurred in universities. To overcome this, the government has issued the PPKS Permendikbud, and the TPKS Law. In fact, the existence of these regulations has not had a significant impact. It is proven that in 2022, there were 49 reports of sexual violence in universities received by the Ministry of Education and Culture's PPKS Working Group. Even as of May 2023, reports regarding sexual violence in universities are still occurring. The purpose of this research is to find an ideal model for overcoming sexual violence in the higher education environment. For this reason, normative legal research is carried out which is prescriptive in nature. Secondary data obtained through library research was processed and analyzed qualitatively. The results of the study show that overcoming sexual violence through regulation alone is still not enough. Because the causes that dominate sexual violence are institutionalized patriarchal culture, unequal social structures, and community stigmatization, the prevention of sexual violence must be accompanied by instilling and cultivating local wisdom values based on morality, ethical behavior, and civility in the dynamics of community interaction.